2016
DOI: 10.1093/mnras/stw2484
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology with AGN dust time lags–simulating the new VEILS survey

Abstract: The time lag between optical and near-infrared continuum emission in active galactic nuclei (AGN) shows a tight correlation with luminosity and has been proposed as a standardisable candle for cosmology. In this paper, we explore the use of these AGN hot-dust time lags for cosmological model fitting under the constraints of the new VISTA Extragalactic Infrared Legacy Survey VEILS. This new survey will target a 9 deg 2 field observed in J-and K s-band with a 14-day cadence and will run for three years. The same… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…In the next few years, deep, wide surveys such as VIDEO and the VISTA Extragalactic Infrared Legacy Survey (VEILS, Hönig et al 2017), which will extend the area of VIDEO, will provide improved constraints on the luminosity function and clustering of high-redshift galaxies, and allowing extension to even more luminous LBGs. By the mid 2020s it should be possible to use the Euclid space telescope mission to do this with 1,000s of LBGs (Bowler et al 2017), which will reveal how the measured large scale structure of LBGs and LAEs relates to reionization.…”
Section: Discussionmentioning
confidence: 99%
“…In the next few years, deep, wide surveys such as VIDEO and the VISTA Extragalactic Infrared Legacy Survey (VEILS, Hönig et al 2017), which will extend the area of VIDEO, will provide improved constraints on the luminosity function and clustering of high-redshift galaxies, and allowing extension to even more luminous LBGs. By the mid 2020s it should be possible to use the Euclid space telescope mission to do this with 1,000s of LBGs (Bowler et al 2017), which will reveal how the measured large scale structure of LBGs and LAEs relates to reionization.…”
Section: Discussionmentioning
confidence: 99%
“…Figure C1 shows the proposed final survey coverage for (left to right) E-CDFS, ELAIS-S1, and XMM-LSS. The blue rectangles show the coverage of the VIDEO (Jarvis et al 2013) or VEILS (Hönig et al 2017) infrared surveys, and are generally representative of the regions that contain the deepest ancillary data from numerous facilities. The labelled pointing centres represent the positions of the final pointing grid, with the circles showing the nominal half-power point of the MeerKAT L-band primary beam at 1284 MHz.…”
Section: Appendix C: Updated Mosaic Layoutsmentioning
confidence: 99%
“…Reverberation mapping (RM) experiments have found that the time lag in the response of the hot dust emission to variations in the optical continuum (τ ) is well enough correlated with the AGN luminosity to lead to the idea of using the hot dust reverberation in AGN as a standardisable candle which could be used to test and constrain cosmological models (e.g. Hönig 2014;Hönig et al 2017).…”
Section: Hot Dust Reverberationmentioning
confidence: 99%